Educational mediation strategies for education on sexually transmitted infections in adolescents - Benavides Leal, Kimberly (2016)
Introduction. This research shows the importance of professional performance in gynecological, obstetric and perinatal nursing education on sexually transmitted infections for the adolescent in schools in Costa Rica, which scientific knowledge is evident on the issue and its interventions education in this social group. Method. It quantitative descriptive research, with a non experimental design, in which the variables described in the study under the first objective was performed. Result. Among the topics of most interest to adolescents are the prevention of sexually transmitted infections, and positions during intercourse, the relevance of these changes by sex, another topic of interest is the onset of sexual relations and like abortion. Conclusion. It is essential to support the professional gynecological, obstetric and perinatal nurses provide in schools on sexually transmitted infections to improve health in this area, and be taught by a qualified person who respects the ethical principles of its practice, so that it generates a reflection teens about their sexual practices from the perspective of disease and health promotion.